Retraction notice to “Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China” [Sci. Total Environ. 898 (2023) 165303] - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2026)

Corrigendum to “maternal smoking during pregnancy could accelerate biological aging in the adulthood: Evidence from a perspective study in UK biobank.” [Sci. Total Environ., 951(2014) 175150] - Wenbo Jiang; Xinyi Sun; Conghui Qiao; Xinyu Shan; Yiwei Tang; Yingdong Zuo; Xinyang Wang; Tianshu Han; Wei Wei (Science of The Total Environment, 2026)

Chrysanthemum classification method via multi-stream deep color space feature fusion - Jian Jiang; Xichen Yang; Hui Yan; Jia Liu; Yifan Chen; Zhongyuan Mao; Tianshu Wang (Computers and Electronics in Agriculture, 2026)

Carbonaceous cores serve as surrogates for environmental particulate matter inducing vascular endothelial inflammation via inflammasome activation - Yán Wāng; Chunzhi Wang; Yang Jiang; Tian Wang; Tianshu Wu; Meng Tang (Journal of Hazardous Materials, 2025)

circPRMT10 regulated by QKI hypermethylation attenuates lung tumorigenesis induced by tobacco carcinogen NNK - Xietian Xiao; Yadong Li; Tianshu Lin; Yufei Liu; Hengfa Zheng; Yanhu Liu; Zhikang Chen; Yihui Ling; Yiguo Jiang; Qiuhan Hua (Journal of Hazardous Materials, 2025)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

Shaking table test of prefabricated equipment cabins with a resilient steel frame at the bottom - Yulong Feng; Zhihao Zeng; Qing Jiang; Tianshu Zeng; Xun Chong; Junqi Huang (Engineering Structures, 2025)

Maternal smoking during pregnancy could accelerate aging in the adulthood: evidence from a perspective study in UK Biobank - Wenbo Jiang; Qianqian Lei; Wei Gao; Xinyi Sun; Conghui Qiao; Xinyu Shan; Yiwei Tang; Yingdong Zuo; Xinyang Wang; Tianshu Han; Wei Wei; Dandan Zhang (Science of The Total Environment, 2024)

The influence of mudstone lithofacies sedimentation on the development of shale oil “sweet-spot intervals” within large down-warped lacustrine basins in China - Youliang Feng; Zhi Yang; Wenqi Jiang; Hong Zhang; Tianshu Zhang; Chang Liu; Pan Li; Jichang Zhu; Xiaoni Wang (Marine and Petroleum Geology, 2024)

Onset of flash drought based on the WRF in the Poyang Lake Basin of China - Chao Deng; Tianshu Lin; Yao Zhuang; Yinchi Zhang; Xiaojun Guan; Lizhi Jiang; Ying Chen; Lu Gao (Atmospheric Research, 2024)

Stability and 3D-printing performance of high-internal-phase emulsions based on ultrafine soybean meal particles - Haiqiang Liao; Tianshu Jiang; Lei Chen; Guozhen Wang; Qian Shen; Xiuying Liu; Wenping Ding; Lijie Zhu (Food Chemistry, 2024)

Transformation mechanisms of antidepressants in biological wastewater treatment: Removal kinetic, transformation products and pathways - Gang Wu; Ruijing Yao; Yi Zhang; Ming Ying; Tianshu Wu; Wenqi Jiang; Depeng Wang; Xu-Xiang Zhang (Chemical Engineering Journal, 2024)

RETRACTED: Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2023)

Corrigendum to “Chemical drivers of ozone change in extreme temperatures in eastern China” [Sci. Total Environ. 874 (2023) 162424] - Xue Meng; Jiakui Jiang; Tianshu Chen; Zekun Zhang; Bingqing Lu; Chao Liu; Likun Xue; Jianmin Chen; Hartmut Herrmann; Xiang Li (Science of The Total Environment, 2023)

Chemical drivers of ozone change in extreme temperatures in eastern China - Xue Meng; Jiakui Jiang; Tianshu Chen; Zekun Zhang; Bingqing Lu; Chao Liu; Likun Xue; Jianmin Chen; Hartmut Herrmann; Xiang Li (Science of The Total Environment, 2023)

Dysregulation of the microbiota-brain axis during long-term exposure to polystyrene nanoplastics in rats and the protective role of dihydrocaffeic acid - Wenbo Jiang; Cong Hu; Yunyan Chen; Yue Li; Xinyi Sun; Huanyu Wu; Ruiming Yang; Yiwei Tang; Fengru Niu; Wei Wei; Changhao Sun; Tianshu Han (Science of The Total Environment, 2023)

What are the Lacustrine Fine-Grained Gravity Flow Sedimentation Process and the Genetic Mechanism of Sweet Sections for Shale Oil? - Caineng Zou; Youliang Feng; Zhi Yang; Wenqi Jiang; Songqi Pan; Tianshu Zhang; Xiaoni Wang; Jichang Zhu; Jiarui Li (Journal of Earth Science, 2022)

Temperature Field in Bone During Robotic Dental Implant Drilling: Theoretical Models and In Vitro Experiments - Qi Cui; Russell Wang; Lisa-Marie Faller; Tianshu Kan; Xianfeng Jiang; Fudong Zhu; Weidong Zhu; Yunfeng Liu (Journal of Medical and Biological Engineering, 2022)

Localization of QTL for cold tolerance at the germination stage of rice (Oryza sativa L.) using recombinant inbred lines - Liangzi Cao; Shukun Jiang; Guohua Ding; Tongtong Wang; Liangming Bai; Jinsong Zhou; Yu Luo; Tianshu Xia; Hui Jiang; Kai Liu; Xueyang Wang; Guang Yang; et al. (Genetic Resources and Crop Evolution, 2022)
The cold tolerance of germinating direct-sown rice ( Oryza sativa L.) has an increased rate of emergence, which ensures vigorous seedling growth. Research on QTL localization for cold tolerance at the germination stage can assist in molecular marker-assisted selection and enhance breeding efficiency. In this study, 94 populations of recombinant self-incompatible lines from Heigu and Ha 9366 were selected to investigate germination rates at low temperatures. It was found that two QTL loci (qLTG-3 and qLTG-12) were located at different germination times on chromosomes 3 and 12, respectively. The two QTLs at three different germination times, located using QTL, accounted for 21.3–25.9% of the phenotypic variation. Moreover, a reciprocal effect was detected between the two QTLs. The double QTLs increased the germination rate by 22–27% in this population. Additionally, qLTG-12 improved cold tolerance at the seedling stage. The results of this study might provide the materials and molecular markers for future molecular marker-assisted breeding for cold tolerance at the germination stage.

Dichloroacetic acid-induced dysfunction in rat hippocampus and the protective effect of curcumin - Wei Wei; Qiuying Dong; Wenbo Jiang; Yue Wang; Yingying Chen; Tianshu Han; Changhao Sun (Metabolic Brain Disease, 2021)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)